T-tube enterostomy in the management of apple-peel atresia: A case series from a single center - Rashwan, Hayssam; Kotb, Mostafa (Frontiers in Pediatrics, 2022)
Background & Objective: Although complex atresias, such as apple-peel and multiple atresias comprise a smaller percentage, they are usually associated with higher incidence of postoperative complications and mortality rate. The management of apple-peel atresia remains more sophisticated. Decompressive and functionalizing stomas are sometimes mandatory to overcome increased wall thickness and the wide disparity among the anastomotic ends. Few reports discussed using tube enterostomy in the management of apple-peel atresia; nonetheless, no previous prospective studies were conducted to discuss its efficacy on a larger population. In this study, we are describing our experience using this technique on 12 patients suffering from apple-peel atresia in our center. Methods: A prospective study was conducted from June 2015 till May 2020, where all children who were found to have apple-peel atresia intraoperatively were included in the study. T-tube was inserted through an enterotomy in the dilated and hypertrophic proximal part, approximately 10 cm away from the anastomosis, and was secured with double suture (Stamm technique) before closing the anterior face of the anastomosis. The short distal limb of the T-tube was directed toward the anastomosis, whilst the long proximal limb was oriented proximally. After finishing the anastomosis, the T-tube was exteriorized through the abdominal wall, fixing the enterostomy and the proximal dilated jejunum against the anterior abdominal wall. Results: A total of 12 cases were encountered throughout the period of study. The mean age at operation of 4 days and mean birth weight of 2700 gram. The mean time for starting oral feeding postoperatively and T-tube removal was 8 and 10.5 days, respectively. Cases were discharged after a mean of 22 days. As regards morbidity and mortality, a single case developed skin excoriations at the site of tube insertion and was managed conservatively using topical ointments and another case died from overwhelming sepsis three days after the operation. Conclusion: T-tube enteroplasty is a safe and feasible option in the surgical management of apple-peel atresia. The main strength of our study is its prospective nature and that it includes apple-peel atresia cases only. However, the main limitation is that a larger sample is needed.